Radiating Fröhlich system as a model of cellular electromagnetism - Šrobár, Fedor (Electromagnetic biology and medicine, 2015)
Oscillating polar entities inside the biological cells, most notably microtubules, are bound to emit electromagnetic radiation. This phenomenon is described by Fröhlich kinetic equations expressing, in terms of quantum occupancy numbers of each discrete collective oscillatory mode, the balance between incoming metabolic energy flow and losses due to linear and non-linear interactions with the thermal environs of the oscillators. Hitherto, radiation losses have not been introduced as part of the balance; it was assumed that they were proportional to the modal occupation numbers. It is demonstrated that this formulation is incorrect and the radiation losses must be taken into account in the kinetic equations explicitly. Results of a numerical study of kinetic equations, enlarged in this sense, are presented for the case of three coupled oscillators which was shown to evince the essential attributes of the Fröhlich systems. Oscillator eigenfrequencies were chosen, alternatively, to fall into the MHz and the THz frequency domains. It was found that large radiation levels destroy the main hallmark of the Fröhlich systems, the energy condensation in the lowest frequency mode. The system then functions as a convertor of metabolic energy into radiation. At more moderate radiation levels, both energy condensation and significant radiation can coexist. Possible consequences for the cell physiology are suggested.
Keywords: kinetika; termodynamika; Electromagnetic Radiation; Cytoskeleton; Cell Membrane; Elasticity; Fröhlich systems; Guanosine Triphosphate; electromagnetic radiation; Oscillometry; cytoskelet; cell physiology; Models, Biological; pružnost; Thermodynamics; elektromagnetické záření; adenosintrifosfát; oscilometrie; Bioelectromagnetism; Kinetics; biologické modely; buněčná membrána; energy condensation; guanosintrifosfát; Adenosine Triphosphate